The Role of Supporting Training in Lead Climbing Performance at the 2025 National Student Sports Week (POMNAS) - Aspar Aspar; Waskito Aji Suryo Putro; Saiful Anwar (Universitas Hamzanwadi, 2026)
This study aimed to examine the role of supporting training in improving lead climbing performance at the 2025 National Student Sports Week (POMNAS). The identified problems included low aerobic and anaerobic endurance, suboptimal muscle strength, and high competitive anxiety among athletes. The study employed a descriptive qualitative design with participants consisting of one coach and three athletes from the Southwest Papua BAPOMI climbing team. Data were collected through semi-structured interviews, document analysis of training programs, and observation of training sessions. Data analysis used a thematic approach with six phases. The findings showed that supporting training comprising physical conditioning, weight training, and mental training contributed significantly to athlete readiness. Physical conditioning improved endurance and fatigue resistance, weight training enhanced muscular strength and movement control, while mental training strengthened confidence, concentration, and emotional stability under competitive pressure. These three components were mutually reinforcing and integrated within a four-phase periodization program. The achievement of two silver medals and two bronze medals at POMNAS 2025 indicated the practical value of a structured supporting training program. In conclusion, supporting training should be regarded as an integral element of lead climbing preparation because it strengthens physical, technical, and psychological readiness for athletes to achieve optimal performance at national competitions.